An assessment on early warning system : Initial survey analysis. - Mohd. Hussain, Mohd. Ramzi; Zen, Ismawi; Rabe, Noor Suzilawati; Tukiman, Izawati; Sabri Muda, Rahsidi; Mamat, Ahmad Fadhli (2019)
In Cameron Highland, Lembah Bertam area and further downstream villages in Susu Dam area are prone and vulnerable to the highest occurrence of floods especially during monsoon season. Thus, Early Warning System (EWS) were set up to avoid or to reduce the impact of natural hazard turns disasters such as floods, landslides and storms with the aim to reduce the vulnerability and disaster risks that signifies the effectiveness of EWS in the realisation of affected community. To test the awareness and preparedness of community in the selected area, a questionnaire survey was employed as the data collection method. The questionnaire survey was conducted before the direct engagement on the EWS information with the community. Using the mixed sampling method of cluster random sampling, a total of 800 respondents from 11 villages, and 5 main ethnicity groups were involved in the survey. From the result, there was a positive relationship showing that respondents who claimed they knew about the EWS from information signage were those from the older age category and earning higher monthly income. On the other hand, there is a negative relationship between respondents’ age and monthly income against other sources that indicates respondents who claimed they knew about the EWS from other sources were those in the younger age category and have low monthly income.